The Rural Family Medicine Café Project: A Social Media Strategy to Reduce Occupational Isolation and Improve Support for Rural Healthcare Professionals - Wheatley, Amber; Floss, Mayara; Bakola, Maria; Kampouraki, Maria; Silveira, Bianca; Scott-Jones, Jo (Frontiers in Public Health, 2020)
Background: Globally rural medicine is currently suffering from staff shortages. Social and professional isolation are identified as significant pressures on health professionals working in rural areas. Social media (SOME) has created new methods of social engagement where conventional forms have failed. The Rural Family Medicine Café (RFMC) is a SOME project created to engage and support those interested in rural family medicine thus decreasing occupational isolation. Methods: A quantitative analysis of SOME activity associated with the RFMC was done by measuring the frequency of #ruralcafe, #ruralwomenGP, #ruralGP, #ruralstories, and #ruralmedicine from October 2015 to October 2016 along with the number of Facebook page likes and YouTube views. A time series and regression analysis were done to assess the correlation between the frequencies of hashtag use and the number of new likes or views. A qualitative analysis of the content of tweets using the associated hashtags and comments on the RFMC YouTube videos was then done to assess participants' response to the RFMC. To add context to the data collected, regularly attending participants were invited for a semi-structured interview. Results: There was a positive trend in the number of Facebook page likes (+273%) and Twitter hashtag use (+2,458%) but a negative trend (−92%) in the number of RFMC YouTube views. There was no statistically significant relationship between the number of views on the RFMC YouTube and RFMC associated SOME activity (p = 0.141). A significant relationship was shown between the number of Facebook page likes and the number of views on the RFMC YouTube (p = 0.037). Participants felt positively about the RFMC with recurring themes of; promotion, advocacy, public health, engagement, inspire, sharing, spreading information, feeling connected and general positive comments such as “enjoying tweets,” “great discussion.” Participants shared anecdotes, useful links, and book recommendations. Conclusion: The RFMC has seen an increase in the amount of associated SOME activity despite having less viewers. This is most likely due to the few participants of the RFMC continuing the café discussions on SOME, particularly Twitter, and engaging outside of the RFMC. The RFMC has developed into a virtual community which is reducing occupational isolation for its participants.